PCM-based solar thermal collectors - Tan, James Yue Xiang. (2011)
The modern world today, with its rapidly increasing population and the upraising of developing countries has resulted in an ever-increasing demand for energy. With the rapid depletion of conventional fuels such as oil, coal and natural gases, extensive research on other means of producing energy has been done, and solar energy is one of the main topics being studied. As such, solar collectors which absorbs the light energy from the sun and converts it into heat energy has been extensively studied and fabricated as an alternative means of water heating, leading to savings in costs and also increased efficiency. The objective of the project is to develop a solar thermal collector with phase change material (PCM) and investigate the performance of a PCM against air as the heat storage medium. The possibility of commercializing a PCM-based solar collector for water heating purposes will be evaluated. The project will involve improving on the design that was done previously. From the experimental results, the PCM proves to be a better heat storage medium than air. Theoretically, if the size of the collector plate was larger and more PCM were used, the effects would be more prominent. Thus the prototype proves that a workable system of a larger size is both theoretically and technically possible although it may not be economically viable to do so. Taking into consideration the other disadvantages such as non-flexible timing of usage, large installation space needed and unreliability due to unpredictable weather, the system appears to be not commercially viable in Singapore at the present moment. However with the possibility of 3 cost becoming lower and efficiency of collector improving in the future, there may be a possibility that PCM will become an important tool to bridge the gap between fuel shortages and rising energy demand in the future.